EDIII-DENV3 nanospheres drive immature dendritic cells into a mature phenotype in an in vitro model - Nattika Nantachit (2018)
© 2017 The Societies and John Wiley & Sons Australia, Ltd Domain III of E protein of dengue virus (DENV) is a target for vaccine development. Unfortunately, this protein based platform has low general immunogenicity. To circumvent this problem, the use of an adjuvant-nanoparticle delivery system to facilitate immunogenicity of soluble DENV-EDIII protein was investigated. One of the key features of this delivery system is its ability to simultaneously deliver antigens and exert adjuvanticity on specialized immune cells. In this study, N-trimethyl chitosan (TMC) nanoparticles (NPs) were generated to be used as adjuvant and carrier for soluble E-domain III of dengue virus serotype 3 (sEDIII-D3). Using ionotropic gelation, purified sEDIII-D3 was encapsulated into TMC NPs to form EDIII-D3 TMC NPs. After optimization, EDIII-D3 TMC particles exhibited a loading efficiency of 81% and a loading capacity of 41%. The immunogenicity of EDIII-D3 TMC NPs was tested using monocyte-derived dendritic cells (MoDCs). It was found that EDIII-D3 TMC NPs were well taken up by MoDCs. In addition, EDIII-D3 TMC NP treated MoDCs significantly upregulated maturation markers (CD80, CD83, CD86 and HLA-DR) and induced secretion of various cytokines and chemokines (IFN-α, IL-1β, IL-6, IL-2, IL-12p70, IFN-γ, IL-4, IL-10, IL-8, MCP-1, macrophage inflammatory protein-1β, granulocyte-colony stimulating factor, granulocyte–macrophage colony-stimulating factor and IL-7). These results indicate that EDIII-D3 TMC NPs are potent immunogens, at least in vitro, with the ability to induce maturation of DCs and highlight the potential use of TMC NPs for enhancing immunogenicity of a non-replicating dengue vaccine.